Assessment of the Efficiency of the Bank’s Lending Policy - Kruhliakova Vira V.; Prokopchuk Sofiia V. (Problemi Ekonomiki)
The lending policy of a commercial bank is a key element of its strategic management, which determines the principles of granting loans, risk assessment and setting interest rates. In a dynamic financial environment, banks are forced to adapt their strategies to ensure stability and competitiveness, taking into account economic conditions, regulatory requirements and technological innovations. This requires constant monitoring of market changes and the introduction of innovative approaches to minimize risks and increase the efficiency of lending activities. The article is aimed at assessing the efficiency of the lending policy of a banking institution in a dynamic economic environment and determining the main directions of its improvement to ensure the stability of the banking system, reduce lending risks and support economic growth. The article substantiates the need to form an effective lending policy of the bank in the conditions of modern economic instability, which is an important factor for ensuring the stability and efficiency of the bank. The lending policy of JSC «BANK UKRAINIAN CAPITAL» has been analyzed, namely the volume of loans granted and their structure, no less important is the analysis of reserves created for possible lending losses, the share of loans in the bank’s assets has been calculated, which made it possible to assess the level of risk and stability of the financial institution. The article analyzes the efficiency of the lending policy, specially: the main indicators of profitability and risk of the bank’s loan portfolio are calculated, which allow to carry out a detailed analysis of the efficiency of lending and identify potential risks that may negatively affect the financial stability of the bank. On the basis of the carried out analysis, recommendations for improving the lending policy of JSC «BANK UKRAINIAN CAPITAL» are formulated, aimed at reducing risks, improving the quality of the loan portfolio and ensuring sustainable economic development of the bank in an unstable market.